Nonlinear optics and optical physics. - Iam-Choon Khoo
This book consists of contributions by leading authorities in nonlinear optics and optical physics. The topics covered include fundamental theories and formalisms on nonlinear optics and current topics of interest in optical physics, as well as more specialized subjects such as phase conjugation, nonlinear guided waves, parametric oscillators and some novel materials. The coverage is comprehensive and pedagogical in nature